The effects of Modulo Activo Recreo Activo (MARA), a physical activity intervention potentiated with SMS, on the cohesion of the networks of public schools of Bogotá, Colombia (2019)
Childhood is a crucial period for developing healthy lifestyle habits (1). 80% of children world-wide are insufficiently active (2). In Colombia, a middle-income country, PA and healthy behaviors interven-tions have shown to be cost-effective to face the spreading of unhealthy behaviors (3). The use of technology, such as text messages (SMS), has shown the potential to promote healthy lifestyles, cohesion and health-related structural changes (3,4). There is not enough evidence for designing community-based interventions based on the use of information and communication technologies (ICT) to efficiently target social network structures. The aim of this paper is to evaluate the effect of the program Modulo Activo Recreo Activo (MARA), a PA intervention, potentiated using ICT, in terms of social cohesion and health-related behaviors using static and temporal social network approaches.